Intra-cardiac pressure drop and flow distribution of bicuspid aortic valve disease in preserved ejection fraction - Aliabadi, Shirin; Sojoudi, Alireza; Bandali, Murad F.; Bristow, Michael S.; Lydell, Carmen; Fedak, Paul W. M.; White, James A.; Garcia, Julio (Frontiers in Cardiovascular Medicine, 2022)
Background: Bicuspid aortic valve (BAV) is more than a congenital defect since it is accompanied by several secondary complications that intensify induced impairments. Hence, BAV patients need lifelong evaluations to prevent severe clinical sequelae. We applied 4D-flow MRI for in detail visualization and quantification of in vivo blood flow to verify the reliability of the left ventricular (LV) flow components and pressure drops in the silent BAV subjects with mild regurgitation and preserved ejection fraction (pEF). Methods: A total of 51 BAV patients with mild regurgitation and 24 healthy controls were recruited to undergo routine cardiac MRI followed by 4D-flow MRI using 3T MRI scanners. A dedicated 4D-flow module was utilized to preprocess and then analyze the LV flow components (direct flow, retained inflow, delayed ejection and residual Volume) and left-sided (Left Atrium (LA) and LV) local pressure drop. To elucidate significant diastolic dysfunction in our population, transmitral early and late diastolic 4D flow peak velocity (E-wave and A-wave, respectively), as well as E/A ratio variable, were acquired. Results: The significant means differences of each LV flow component (global measurement) were not observed between the two groups (p>0.05). In terms of pressure analysis (local measurement), maximum and mean as well as pressure at E and A-wave timepoints at the mitral valve (MV) plane were significantly different between BAV and control groups (p: 0.005, p: 0.02, and p: 0.04 and p: <.001; respectively). Furthermore, maximum pressure and pressure difference at the A-wave timepoint at left ventricle mid and left ventricle apex planes were significant. Although we could not find any correlation between LV diastolic function and flow components, Low but statistically significant correlations were observed with local pressure at LA mid, MV and LV apex planes at E-wave timepoint (R: -0.324, p: 0.005, R: -0.327, p: 0.004 and R: -0.306, p:0.008 respectively). Conclusion: In BAV patients with pEF, flow components analysis is not sensitive to differentiate BAV patients with mild regurgitation and healthy control because flow components and EF are global parameters. Inversely, pressure (local measurement) can be a more reliable biomarker to reveal the early stage of diastolic dysfunction.